1991
DOI: 10.1213/00000539-199109000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate Hypotension With Nicardipine or Nitroprusside During Total Hip Arthroplasty

Abstract: To induce deliberate hypotension during anesthesia, nicardipine was administered to patients undergoing total hip arthroplasty and was randomly compared with nitroprusside. Hemodynamic measurements were performed before and 10, 20, 30, and 60 min after starting to administer either nicardipine (n = 12) or nitroprusside (n = 12) (B, T1, T2, T3, and T4, respectively); at the end of drug infusion (T5); and 10, 20, and 60 min later (T6, T7, and T8, respectively). Plasma renin activity and catecholamine levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Seventy articles were found relevant to this topic: 16 were randomized clinical trials [17][18][19]46 166,170,172,174,195,196 , 2 retrospective case Inadequate size per group 3 Patient selection was not consecutive and complete Did not describe method of randomization Did not mention duration of anaesthesia and induced hypotension * 1 = low risk of bias; 2 = moderate risk of bias; 3 = high risk of bias. Inadequate size per group 3 Patient selection was not consecutive and complete Did not describe method of randomization Did not mention duration of anaesthesia and induced hypotension * 1 = low risk of bias; 2 = moderate risk of bias; 3 = high risk of bias.…”
Section: Cardiovascular Effects Of Hypotensive Anaesthesiamentioning
confidence: 99%
“…Seventy articles were found relevant to this topic: 16 were randomized clinical trials [17][18][19]46 166,170,172,174,195,196 , 2 retrospective case Inadequate size per group 3 Patient selection was not consecutive and complete Did not describe method of randomization Did not mention duration of anaesthesia and induced hypotension * 1 = low risk of bias; 2 = moderate risk of bias; 3 = high risk of bias. Inadequate size per group 3 Patient selection was not consecutive and complete Did not describe method of randomization Did not mention duration of anaesthesia and induced hypotension * 1 = low risk of bias; 2 = moderate risk of bias; 3 = high risk of bias.…”
Section: Cardiovascular Effects Of Hypotensive Anaesthesiamentioning
confidence: 99%
“…With the use of various vasodilating agents, such as nitroprusside [13][14][15][16][17], nitroglycerin [16], and nicardipine [13,17], to induce hypotension, these results also have suggested a role for renin-angiotensin system in blood pressure maintenance. Multiple factors are known to be involved in renin release [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SNP has been shown to exert a powerful dilating effect on both resistance vessels and veins [16]. In addition, in patients receiving induced hypotension with nicardipine or SNP during total hip arthroplasty, Bernard et al [3] have shown that the intravenous fluid volume required to maintain pulmonary capillary wedge pressure at 5mmHg was larger in the SNP group than in the nicardipine group, which indirectly indicates that nicardipine has less of a dilatory effect on the venous system than SNP. However, there have been no studies examining the direct effect of nicardipine on MCFP in comparison with SNP at comparable hypotensive levels.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, nicardipine, a dihydropyridine calcium channel blocking agent, is widely used for the treatment of hypertension. It has recently been reported that nicardipine can be used for induced hypotension under anesthesia in patients undergoing orthopedic surgery [2,3]. These human studies have compared hemodynamic changes during hypotension induced by SNP and nicardipine [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation